STRATEGI KOMUNIKASI PEMASARAN BERBASIS SOSTAC PADA KELOMPOKTANI LEBAH MADU KELULUT DALAM UPAYA OPTIMALISASI PROMOSI DAN PENGUATAN KEMITRAAN PASAR: STRATEGI KOMUNIKASI PEMASARAN BERBASIS SOSTAC PADA KELOMPOKTANI LEBAH MADU KELULUT DALAM UPAYA OPTIMALISASI PROMOSI DAN PENGUATAN KEMITRAAN PASAR - I Putu Gede Didik Widiarta; Made Hardinata Wijakesuma; Dinar Anindyasari; Muhammad Eriansyah Al Hakim; Amalina Nur Wahyuningtyas (Universitas Boyolali, 2026)
The stingless bee honey agribusiness in Indonesia demonstrates strong economic potential but faces constraints in effective promotion and sustainable market network expansion. This study aims to analyze the implementation of a SOSTAC-based (Situation, Objectives, Strategy, Tactics, Action, and Control) marketing communication strategy among stingless bee farmer groups in Samarinda to optimize promotion and strengthen market partnerships. A descriptive qualitative method was employed, with data collected through field observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model and validated through triangulation of sources and methods. The results revealed that 30 stingless bee farmer groups operate in Samarinda, of which only 41% utilize digital media for promotion. Implementation of the SOSTAC-based strategy increased brand awareness by 33%, online sales by 35%, and active partnerships by 67%. The most effective strategies included ecological digital storytelling, localized visual branding, and collaboration with culinary SMEs and online marketplaces. The SOSTAC-based communication strategy has proven effective in improving promotional performance, expanding partnerships, and strengthening the position of stingless bee honey as a competitive and sustainable local agribusiness product.